2016
DOI: 10.1259/bjr.20160028
|View full text |Cite
|
Sign up to set email alerts
|

Utility of pre- and post-MR arthrogram imaging of the shoulder: effect on patient care

Abstract: Objective: MR arthrogram imaging of the shoulder is considered more accurate in assessing shoulder pathology than conventional MRI. Arthrography is a minimally invasive procedure. However, most patients prefer to have conventional MRI rather than MR arthrogram imaging. We report the benefit of assessing pre-arthrogram conventional MRI, to determine whether an MR arthrogram is needed for further evaluation. Methods: 100 consecutive conventional shoulder MR and MR arthrography examinations performed on the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…On higher field 3.0 Tesla MRI systems, non-contrasted MRI is generally performed as the initial evaluating imaging modality for SLAP tears, even in these younger patients. However, if the initial 3.0 Tesla MRI is negative or equivocal, as in our patient, arthrogram may increase sensitivity for SLAP diagnosis [5]. In selected clinical scenarios, arthrogram may also be useful for assessing full-thickness rotator cuff pathology, undersurface rotator cuff tearing, loose bodies and synovitis or to assess a post-surgical shoulder [6].…”
Section: Discussion Clinical and Imaging Findingmentioning
confidence: 79%
“…On higher field 3.0 Tesla MRI systems, non-contrasted MRI is generally performed as the initial evaluating imaging modality for SLAP tears, even in these younger patients. However, if the initial 3.0 Tesla MRI is negative or equivocal, as in our patient, arthrogram may increase sensitivity for SLAP diagnosis [5]. In selected clinical scenarios, arthrogram may also be useful for assessing full-thickness rotator cuff pathology, undersurface rotator cuff tearing, loose bodies and synovitis or to assess a post-surgical shoulder [6].…”
Section: Discussion Clinical and Imaging Findingmentioning
confidence: 79%
“…8 ). Multiple meta-analyses have shown that dMRA is more accurate than cMRI for the diagnosis of SLAP tears [ 181 , 182 , 191 , 192 ], with higher diagnostic accuracy at 3 T over 1.5 T with or without intra-articular contrast material [ 181 ]. One meta-analysis evaluating 3 T studies showed that dMRA was similar in sensitivity to cMRI (0.84 vs 0.83, p=.575), but less specific (0.99 vs 0.92 p < 0.0001) for SLAP lesions [ 177 ].…”
Section: Joint-specific Indicationsmentioning
confidence: 99%
“…MRI has less sensitivity in detecting labral pathology as compared with MRI arthrogram. 8 The use of a 3-T magnet may differ from that used by some in practice, and thus our imaging, and incidence of detected abnormalities, may be different. In addition, there was no arthroscopic confirmation of the MRI findings, but the lack of surgical data simulates the decision-making assessment scenario, with just clinical and MRI findings.…”
Section: Discussionmentioning
confidence: 99%